3D Modeling and Printing of Everyday Objects Designed in GeoGebra AR - Flores Osorio, Alejandro Isaías (2024)
The present research is a didactic proposal for modeling real objects through bounded surfaces using GeoGebra AR for engineering programs, which seeks to contribute to the improvement of the design of the learning sessions of the variable calculation courses, showing two cases of modeling everyday objects such as bottles and flowers. These designs will be 3D printed with the purpose of relating mathematical objects to concrete material. The development of these modeling requires knowledge of surfaces and surface parameterization, as well as notions of using GeoGebra. This would allow students to develop their geometric reasoning and the ability to sketch surfaces, leaving behind the classic theoretical calculus tasks and allowing students to find objects in their environment that they can model in addition to interacting with their environment with augmented reality that this software presents in its GeoGebra AR version and to manipulate the specific material through 3D printing. Finally, it is concluded that the application of these activities could help achieve the achievement of the competencies and capabilities of the course, and this can be seen reflected in the academic performance of the students.